After the third way : the future of social democracy in Europe - Cramme, Olaf.; Diamond, Patrick; Policy Network (New York : I.B. Tauris, 2012)
'The social democratic parties were once the strongest political forces in Europe. Today, however, they appear disorientated and rudderless, crucially lacking the ideological, intellectual and organisational vitality which underpinned their strength in the post-war political landscape. Electorally marginalised, seemingly ideologically exhausted and often out-of-step with the contemporary zeitgeist, European social democracy is currently in profound need of revision and renewal-potentially its very existence as a political force is under threat. This book marks a serious attempt to forge the intellectual backbone of a renewed social democracy fit for the twenty-first century. Bringing together leading academics, political thinkers and policy experts, it offers a new and original perspective on ideological and policy innovation and will be invaluable reading for anyone interested in the future of social democracy.'--Publisher's website.
'Policy network'--Cover ;'About Policy Network'--P. [v].
Includes bibliographical references (p. [255]-272) and index.
Keywords: Socialism -- Europe; Mixed economy -- Europe; Welfare state -- Europe